IMPLEMENTASI MEDIA PEMBELAJARAN INTERAKTIF LOTRE PANCASILA UNTUK MENINGKATKAN PARTISIPASI BELAJAR PESERTA DIDIK MATA PELAJARAN PENDIDIKAN PANCASILA - Natalia, Erina; Didik Iswahyudi; Yulius Rustan Effendi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines how interactive learning media, such as lottery games, can be used to increase student engagement in citizenship education. The impetus for the research was the recognition of a pressing concern: a lack of student engagement in the learning process. This issue has been identified as critical and requires immediate attention. The study launched a decisive effort to effectively resolve the issue of low student engagement, which had been identified as a key challenge. Traditional teaching methods that emphasize the teacher, combined with a lack of interactive learning resources, greatly diminish educational effectiveness. Therefore, this study focuses on creating a game-based learning experience that is student-centred, engaging, enjoyable, and meaningful. A qualitative descriptive approach was employed involving secondary school students and citizenship education teachers from Malang Regency. Data collection techniques included observation, interviews, and documentation. The robust Miles and Huberman interactive model was used to analyse the data, seamlessly integrating data reduction, presentation, and conclusion. This model encompasses all three processes. The research findings demonstrate that the Pancasilan lottery game increases student participation in cognitive, affective, and social learning. Students demonstrated increased motivation to learn, improved critical thinking skills, greater confidence in expressing their opinions, and greater involvement in discussions and group work. This method creates a more interactive, collaborative, and engaging learning environment. Its creativity and positive impact make this method increasingly popular among educators and students alike. It is also easy to implement as it does not require complex technology. Thus, it positively contributes to improving the quality of education in line with the principles of the Indonesian state.